The Effect of Digital Technology Use on Emotion Regulation of Elementary School Students - Rahayu, Sella; Wulandari, Ayu; Azainil, Azainil (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to examine the influence of digital technology use on the emotional regulation of elementary school students. The background of this research stems from the increasing intensity of digital device usage among children, which can have both positive and negative impacts on their emotional development. This research employed a quantitative approach, and data were collected through structured questionnaires distributed to fifth-grade students at SDN 008 Sungai Kunjang. The results indicate that most students responded positively to the use of digital technology in helping them recognize, manage, and express their emotions more effectively. The use of digital tools has been shown to support emotional regulation, particularly in areas such as social interaction and self-control. However, some students did not fully experience these benefits, highlighting the need for ongoing guidance from teachers and parents. The implications of this study underscore the importance of integrating digital technology effectively into the learning process, accompanied by adequate supervision, to support students' social-emotional development optimally.